G193 The Role of Acute Respiratory Events in Child Deaths Due to Neurological Conditions and Congenital Anomalies. (4th June 2013) - Davey, J; Hardelid, P; Dattani, N; Gilbert, R
Abstract : Aims: To determine the role of acute respiratory events mentioned on death certificates of children dying of a neurological condition or a congenital anomaly in the UK. Methods: Data on causes of death, extracted from death certificates from 11262 children who died between 2006 and 2010 aged one to 18 years, were obtained from national statistics agencies in England and Wales, Scotland and Northern Ireland. We scrutinised all causes of death for children whose underlying cause was a neurological/perinatal condition or a congenital anomaly to determine whether an acute respiratory event had occurred. An acute respiratory event was defined as acute upper and lower respiratory tract infections and acute respiratory failure. The proportion of children whose death certificate mentioned an acute respiratory event was estimated overall and by age-group (1–4, 5–9, 10–14 and 15–18 years). Results: 1433 children died from a neurological/perinatal condition and 867 children died from a congenital anomaly in the study period, representing 12.7% and 7.7% of all deaths. Among children dying of a neurological/perinatal condition, 470 (32.8%) death certificates mentioned an acute respiratory event. The prevalence of acute respiratory events varied by age, from 78/470 (16.6%) in 5–9 year olds to 154/470 (32.8%) in 1–4 year olds. Among children dying of a congenital anomaly, 201 death certificates mentioned an acute respiratory event (23.2%). Prevalence ranged from 29/201 (14.4%) in 10–14 year olds to 99/201 (49.3%) in 1–4 year olds. Overall, the most common acute respiratory events were unspecified pneumonia, recorded on 11.7% of death certificates (268 of 2300), unspecified bronchopneumonia, recorded on 10% (228 of 2300) and unspecified respiratory failure recorded on 9.3% (214 of 2300). Conclusions: Acute respiratory events are common contributing causes of death among children dying from neurological/perinatal conditions or congenital anomalies. Such events may represent a failure of chronic care or be part of an expected, planned death. Further research is needed to determine how to distinguish between these pathways of care.